Sequential appearance and ultrastructure of amphophilic cell soci, adenomas, and carcinomas in the liver of male and female rats treated with dehydroepiandrosterone - Metzger, Christel; Mayer, Doris; Hoffmann, Herbert; Bocker, Thomas; Hobe, Gerhard; Benner, Axel; Bannasch, Peter (Toxicologic pathology, 1995)
Dehydroepiandrosterone (DHEA), a hormone of the adrenal cortex, acts as a peroxisome proliferator and hepatocarcinogen in rats upon long-term treatment with high doses in the diet. The aim of the present study was to identify the site of origin of hepatocellular neoplasms and the sequence of preneoplastic lesions. Twenty-five female and 25 male rats were given 0.6% DHEA in the diet; 25 animals of each sex were controls. Groups of 5 treated and untreated animals were sacrificed after 4, 20, 32, 70, and 84 wk. Amphophilic cell foci were detected after 32 wk of treatment; they developed from the liver parenchyma almost exclusively in the vicinity of portal tracts. Adenomas of the amphophilic or amphophilic/tigroid cell phenotype were observed at 70 wk of treatment. Highly differentiated hepatocellular carcinomas presenting a similar cellular phenotype occurred after 70-84 wk. The incidence of hepatocellular carcinomas was 44% in female and 11% in male rats. Ultrastructural studies of the amphophilic cell foci and tumors revealed a marked proliferation of mitochondria and a moderate proliferation of peroxisomes in all lesions. In addition, a very strong peroxisome proliferation was observed in perivenular hepatocytes in the liver of female rats. Peroxisomes usually lacked core and showed flocculent matrices. In male rats, weak peroxisomal proliferation was observed. Typical morphological abnormalities of these peroxisomes were paracrystalline inclusions of striated appearance. Although the most prominent peroxisome proliferation was observed in perivenular hepatocytes, these cells did not seem to be involved in tumor development. In contrast, the morphological similarity of the amphophilic cell foci and the amphophilic/tigroid cell adenomas and carcinomas, their coincident localization near portal tracts, and the sequential appearance of these lesions suggest that the amphophilic cell foci represent an early stage in DHEA-induced hepatocellular neoplasia. Mitochondrial proliferation as the most prominent feature in all stages of this model of hepatocarcinogenesis may offer a new approach for analysis of hepatocarcinogenesis induced by DHEA and possibly other peroxisomal proliferators.